The science and policy of critical loads of pollutant deposition to protect ecosystems in New York. (26th March 2014) - Sullivan, Timothy J.; Jenkins, Jerry
Abstract : We discuss the potential for adopting a critical load (CL) of air pollutant–deposition approach to inform natural resource protection and management in New York. The CL reflects the quantitative exposure to pollutants below which significant harmful effects on specified sensitive elements of the environment do not occur. Here, we discuss how CLs can be used to protect sensitive ecosystems against the harmful effects of atmospheric sulfur and nitrogen deposition and associated soil and water acidification and nutrient enrichment. The CL can be used diagnostically to determine resources at risk and prescriptively to evaluate the effectiveness of regulations and to manage resources.